1994
DOI: 10.1016/0014-5793(94)00411-0
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas phytotoxin coronatine mimics octadecanoid signalling molecules of higher plants

Abstract: The phytotoxic principle, coronatine, which is present in several pathovars of the plant pathogen, Pseudomonas syringae was shown to be highly active in completely different, jasmonate-selective bioassays. At nanomolar to micromolar concentrations, coronatine induced the accumulation of defense-related secondary metabolites in several plant cell cultures, induced transcript accumulation of the elicitor-responsive gene encoding the berberine bridge enzyme of Eschscholtzia califomica, as well as the coiling resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
176
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(188 citation statements)
references
References 18 publications
11
176
0
1
Order By: Relevance
“…The phytotoxin coronatine, produced by several pathovars of Pseudomonas syringae, induced reactions similar to OPDA (Blechert et al, 1999;Koch et al, 1999). Therefore, coronatine is suggested to represent a structural analogue of OPDA (Weiler et al, 1994). Deduced from the structure of coronatine, new synthetic analogs of OPDA have been designed which were expected to mimic OPDA and/or jasmonate activities.…”
Section: Induction Of Glyceollins In Soybean Cell Cultures Treated Wimentioning
confidence: 99%
“…The phytotoxin coronatine, produced by several pathovars of Pseudomonas syringae, induced reactions similar to OPDA (Blechert et al, 1999;Koch et al, 1999). Therefore, coronatine is suggested to represent a structural analogue of OPDA (Weiler et al, 1994). Deduced from the structure of coronatine, new synthetic analogs of OPDA have been designed which were expected to mimic OPDA and/or jasmonate activities.…”
Section: Induction Of Glyceollins In Soybean Cell Cultures Treated Wimentioning
confidence: 99%
“…Furthermore, (-)-JA (1) was shown to occur conjugated with a variety of amino acids in higher plants [2,3]. Several environmental stresses like wounding [4][5][6], electric current application [7], osmotic stress [8], mechanical stress [9] or local burning [7] lead to an endogenous rise of jasmonates, thereby inducing synthesis of specific proteins like proteinase inhibitors in tomato or vegetative storage proteins in soybean (for review cf. [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonate-induced events such as the biosynthesis of glucosinolates [15], ethylene formation [16], tendril coiling [9], or the emission of volatiles [17] were also induced upon treatment with coronatine which can be regarded as an analogue of JA amino acid conjugates [18]. Coronatine is a phytotoxin produced by several pathovars of Pseudomonas syringae, and *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research results indicated that coronatine mimics a precursor of jasmonic acid (JA) which is involved in the biological processes of plant growth and development (Sakai, 1980(Sakai, , 1981Sakai et al, 1984;Ferguson and Mitchell, 1985;Mino et al, 1987;Kenyon and Turner, 1990;Weiler et al, 1993Weiler et al, , 1994. Coronatine affects the accumulation of defenserelated secondary metabolites such as pterocarpantype glyceollin, sakuranetin, momilactone A, alkaloid, volatile materials and taxol (Ichihara and Toshima, 1998;Tamogami and Kodama, 2000;Fliegmann et al, 2003;Lauchli and Boland, 2003).…”
mentioning
confidence: 99%